Tren publikasi collaborative governance sebuah analisis bibliometrik - Ladiatno Samsara (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction: This study aims to analyze publication trends related to collaborative governance indexed in Scopus database from first year of publication until June 2022. Data Collection Methods: Collaboratove Governance field journal articles published between 1977-2022 were searched from the scopus database using "Collaborative Governance” keyword. Data Analysis: This study uses an analysis of publication trends in collaborative governance, the most productive countries and the most productive organizations, Co-Authorship, Co- and Citation. Results and Discussion: Research related to collaborative governance widely are conducted globally. Multistakeholders need to collaborate to solve the challenges. The year 2021 becomes the most productive year with 700 publications. United States and United Kingdom are the two most productive countries. The co-authorship network shows Torfing while Ansell was the most cited author. The Co-Occurrence Network, based on keywords, shows governance, collaboration and collaborative governance. Conclusion: Bibliometric methods can be used to analyze publication trends related to "Collaborative Governance". However, it needs the support of datasets and a complete computing system. The results of the analysis of articles related to collaborative governance there is an increase in publication trends related to collaborative governance.